Pediatric papillary urothelial neoplasm: 18-year single-center experience in diagnosis and treatment - Pei Liu; Xin Li; Jiayi Li; Zonghan Li; Yang Yang; Ning Sun; Hongcheng Song; Weiping Zhang (BMC Urology)
Abstract Objective This study outlines the diagnosis, treatment, and follow-up protocols for pediatric bladder urothelial tumors, sharing insights from clinical experience to assist pediatric surgeons. Method A retrospective analysis was conducted on medical records from January 2006 to January 2024, involving 17 pediatric cases treated at our hospital. The patients were categorized into two groups: Group 1 included children diagnosed with the pathological type “urothelial papilloma” (UP), while Group 2 consisted of those with the pathological type “papillary urothelial neoplasm of low malignant potential” (PUNLMP). The primary outcomes of the study were the presence or absence of recurrence. Results The average age of the patients was 10.5 years, with all patients being male. Gross hematuria was the predominant symptom, observed in 88.2% of cases. All patients underwent a urinary ultrasound examination. Open resection of bladder tumors was performed in 82.3% of patients, while the remainder underwent transurethral resection of bladder tumors (TURBT) surgery. Pathologic findings revealed UP in 11 cases and PUNLMP in 6 cases. The median follow-up duration was 46 months. Two out of the six PUNLMP patients received postoperative chemotherapy with bladder instillation, while the remaining 4 patients did not receive this treatment. Among those not treated, one patient experienced a recurrence 25 months after the initia surgery. Subsequently, the patient underwent a second bladder tumor resection and received intravesical chemotherapy. No recurrences were noted following bladder instillation chemotherapy. Conclusion Children presenting with gross hematuria should be evaluated for bladder urothelial tumors. Timely ultrasonography aids in diagnosis. The prognosis for children with this condition is favorable, although recurrence is possible. Ultrasound monitoring is crucial during follow-up, and prophylactic bladder instillation chemotherapy may be considered for children with PUNLMP to reduce recurrence risk, though further evidence is required to validate this approach. Levels of evidence Level III.